Emerging role of Transvaginal Ovarian Needle Drilling in CC-resistant PCOS: A meta-analytical comparison with LOD - Huzna, Nanda Cynthia; Maulana, Rifqi Fadhil; Deswindra, Mohamad Reihansyah; Saputra, Gede Ardi; Megawati, Melia; Pratama, Muhammad Reqza (Majalah Obstetri & Ginekologi, 2026)
HIGHLIGHTS This meta-analysis compares the effectiveness of transvaginal ovarian needle drilling (TND) versus laparoscopic ovarian drilling (LOD) in clomiphene citrate-resistant PCOS patients, focusing on pregnancy outcomes and ovarian reserve indicators. The findings indicate comparable pregnancy rates between TND and LOD, while TND may offer the advantage of better ovarian reserve preservation and a minimally invasive approach suitable for outpatient settings.   ABSTRACT Objective: Clomiphene citrate-resistant polycystic ovary syndrome (CC-resistant PCOS) remains a therapeutic challenge, often requiring second-line surgical interventions to induce ovulation. Laparoscopic ovarian drilling (LOD) is the standard approach, whereas transvaginal ovarian needle drilling (TND) has emerged as a minimally invasive alternative with potential advantages in preserving ovarian reserve. This study compared the effectiveness and safety of TND versus LOD by evaluating pregnancy rates and postoperative anti-Müllerian hormone (AMH) levels. Materials and Methods: A systematic review and meta-analysis was conducted following PRISMA guidelines. Literature searches were performed in PubMed, Cochrane Library, and ScienceDirect up to June 2025. Studies involving women with CC-resistant PCOS comparing TND and LOD were included. Primary outcomes were pregnancy rates and postoperative AMH levels. Risk of bias was assessed using Cochrane RoB-2 and ROBINS-I tools. Pooled estimates were calculated using a random-effects model. Results: Four studies involving 660 participants were included. The pooled relative risk for pregnancy in the TND group compared to the LOD group was 0.74 (95% CI: 0.39–1.41; p = 0.36; I² = 71%), indicating no statistically significant difference. The mean difference in postoperative AMH levels favored TND (+1.12 ng/mL; 95% CI: -0.06–2.3; p = 0.06; I² = 90%), suggesting a trend toward better ovarian reserve preservation. TND demonstrated comparable pregnancy outcomes with a potential advantage in minimizing ovarian damage. Conclusion: TND may offer similar pregnancy outcomes with better ovarian reserve preservation than LOD; however, further high-quality studies are required to confirm these findings.